Design and Build a Power System on a High-Density Polyethylene Plastic Crusher Machine - Pramudi, Ganjar; Hakim, Ilham Azhar Raihan Rahmanul (Magister Teknik Mesin Universitas Pancasila, 2025)
High Density Polyethylene (HDPE) plastic is one of the plastic materials commonly used for the manufacture of plastic packaging. HDPE plastic waste, which is increasing in number every year, can be used by recycling in a good way. One way to manage HDPE plastic waste is to recycle it into powder for composite materials. HDPE plastic crusher machine is used to chop HDPE plastic waste into small pieces such as powder, thus facilitating the recycling process for composite materials. So this HDPE plastic crusher or crusher machine was designed with a new blade design so that the shredding results can be maximized and use an electric motor with low power so that it can save production costs. The drive used is an electric motor with a power of 3 HP at a speed of 1420 rpm. With a cutting force of 99.3 N.mm2, it is able to produce a fine powder of 100 grams for 60 minutes. The test is divided into 2 types, namely testing without HDPE plastic and with HDPE plastic.